2021
DOI: 10.1007/s12119-021-09896-9
|View full text |Cite
|
Sign up to set email alerts
|

Jagged Love: Narratives of Romance on Dating Apps during COVID-19

Abstract: The romance plot is one of the most pervasive narratives in Western society. It is a cultural masterplot: a story with which almost everyone is familiar, which can deeply and intrinsically shape the way we think about how we live. This article examines how people interact with the romance masterplot and how it affects their search for love on dating apps in Australia during the global pandemic in 2020. Using data drawn from interviews and focus groups, and combining sociological research and narrative theory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
2
7
0
4
Order By: Relevance
“…In fact, our results suggest that couples who do not yet have an established communication repertoire need to negotiate a "communication rhythm" as they cannot rely on an established set of communication practices. Similarly, research findings on dating during COVID-19 emphasize the difficulties in initiating couple relationships during the pandemic (Duguay et al, 2022;Myles et al, 2021;Portolan & McAlister, 2022). With respect to visual communication, this study supports the argument that visuals need to be examined within the practices in which they are embedded.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, our results suggest that couples who do not yet have an established communication repertoire need to negotiate a "communication rhythm" as they cannot rely on an established set of communication practices. Similarly, research findings on dating during COVID-19 emphasize the difficulties in initiating couple relationships during the pandemic (Duguay et al, 2022;Myles et al, 2021;Portolan & McAlister, 2022). With respect to visual communication, this study supports the argument that visuals need to be examined within the practices in which they are embedded.…”
Section: Discussionsupporting
confidence: 75%
“…Third, it is not clear how participants found their romantic partners, whether at parties, or by social networking applications, for example. It is possible that social networking activities have become more prevalent during the COVID-19 pandemic, [20][21][22] but any impact on this study remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of participants, regardless of age, gender or sexual identity, the ideal relationship being sought and/or found was constituted as amorous, romantic, monogamous and ideally lifelong. Some studies have similarly found that traditional discourses of romantic love have been incorporated into dating app practices rather than being eroded (Hobbs et al, 2017;Palmer, 2020;Portolan & McAlister, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The studies above (Hobbs et al, 2017;Portolan & McAlister, 2022;Van Hooff, 2020) focused on their participants' current use of dating apps. Hobbs et al asked questions about participants' expectations of use and sexual activity (2017, p. 276), and Portolan and McAlister asked about their participants' 'usage practices, personal presentation on app, expectations and desires ' (2022, p. 362).…”
mentioning
confidence: 99%